The Unexpected Essentiality of glnA2 in Mycobacterium smegmatis Is Salvaged by Overexpression of the Global Nitrogen Regulator glnR, but Not by L-, D- or Iso-Glutamine - Rakovitsky, Nadya; Bar Oz, Michal; Goldberg, Karin; Gibbons, Simon; Zimhony, Oren; Barkan, Daniel (Frontiers in Microbiology, 2018)
Nitrogen metabolism plays a central role in the physiology of microorganisms, and Glutamine Synthetase (GS) genes are present in virtually all bacteria. In M. tuberculosis, four GS genes are present, but only glnA1 is essential, whereas glnA2 was shown to be non-essential for in-vitro as well as in-vivo growth and pathogenesis, and is postulated to be involved in D-, or iso-glutamine synthesis. Whilst investigating the activity of an antimicrobial compound in M. smegmatis, we found a spontaneous temperature-sensitive mutant in glnA2 (I133F), and used it to investigate the role of glnA2 in M. smegmatis. We deleted the native glnA2 and replaced it with a mutated allele. This re-created the temperature sensitivity – as after 3-4 seemingly normal division cycles, glnA2 become essential for growth. This essentiality could not be salvaged by neither L-, D-, nor iso-glutamine, suggesting an additional role of glnA2 in M. smegmatis over its role in M. tuberculosis. We also found that overexpression of the global nitrogen regulator-activator glnR enabled bypassing the essentiality of glnA2, allowing the creation of a complete deletion mutant. The discrepancy between the importance of glnA2 in Mtb and M. smegmatis stresses the caution in which results in one are extrapolated to the other.